History and Religion: Narrating a Religious Past - Otto, Bernd-Christian; Rau, Susanne; Rüpke, Jörg (De Gruyter, 2015)
This volume is the first systematic scholarly study that analyses the complex relationship between history and religion. It considers religious groups as both producers of historical narratives and topics of historiography. From different disciplinary perspectives, the authors explore how religions are historicised. In so doing, they address the biases and elisions of current analytical and descriptive frames in the history of religion.